2018
DOI: 10.3390/polym10121355
|View full text |Cite
|
Sign up to set email alerts
|

The Drop-in-Drop Encapsulation in Chitosan and Sodium Alginate as a Method of Prolonging the Quality of Linseed Oil

Abstract: Nowadays, the encapsulation of sensitive products by various techniques has become popular as a promising preservation method. In particular, this applies to oils with a high content of unsaturated fatty acids and a high susceptibility to deterioration. This work presents the possibility of using a chitosan and sodium alginate in the form of a hydrogel membrane to protect food ingredients such as linseed oil, which is stored in an aquatic environment. The obtained results showed the high efficiency of the coax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Chitosan (poly-β-(1 → 4)-2-amino-2-deoxy- d -glucose) has the advantage of easy modification (grafting with various functional groups), so it can be easily transformed to the appropriate adsorbent each time. Some of its unique properties such as biocompatibility, biodegradability and non-toxicity, along with its adsorption ability, turn chitosan into a very promising and eco-friendly adsorbent material [26,27,28,29,30], which can be also combined with agro-wastes (coffee) for pharmaceutical removal [31]. Our research team has been extensively studying the use of chitosan in adsorption applications (i.e., for environmental pollutants such as dyes [32,33,34,35,36], heavy metals [37,38,39,40,41,42], and drugs [43]).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (poly-β-(1 → 4)-2-amino-2-deoxy- d -glucose) has the advantage of easy modification (grafting with various functional groups), so it can be easily transformed to the appropriate adsorbent each time. Some of its unique properties such as biocompatibility, biodegradability and non-toxicity, along with its adsorption ability, turn chitosan into a very promising and eco-friendly adsorbent material [26,27,28,29,30], which can be also combined with agro-wastes (coffee) for pharmaceutical removal [31]. Our research team has been extensively studying the use of chitosan in adsorption applications (i.e., for environmental pollutants such as dyes [32,33,34,35,36], heavy metals [37,38,39,40,41,42], and drugs [43]).…”
Section: Introductionmentioning
confidence: 99%
“…They exhibited interesting results in combination with alginate for oil capsule production [39,52]. The addition of chitosan as an additional coating material for kenaf seed oil and ginger oil alginate capsules permitted to reduce the shell porosity [37,39]. This was similarly observed for soy protein isolates added to alginate [38].…”
Section: Reduced Oxidationmentioning
confidence: 81%
“…Several research works have studied the oxidative stability of different oils, with or without antioxidant addition in the hydrophobic phase and with various shell material composition [32,41,47], Oil oxidation was generally evaluated through the determination of the peroxide value (PV) and the anisidine value (p-AV) that indicate primary oxidation and secondary oxidation, respectively [37,49]. According to Table 2, most oils encapsulated by coextrusion had reduced values of oxidation indicators, and for most of them, less bioactives' loss was reported.…”
Section: Reduced Oxidationmentioning
confidence: 99%
“…Similar results have been reported for the inhibition effect of microencapsulation of flaxseed oil with chitosan or sodium alginate on acidity increase. It has been reported that encapsulation with chitosan was more effective in acidity control in flaxseed oil than with sodium alginate [ 21 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%